Net energy content of rice bran, defatted rice bran, corn gluten feed, and corn germ meal fed to growing pigs using indirect calorimetry() - Lyu, Zhiqian (J Anim Sci, 2018)
The objective of this experiment was to determine the effects of increased fiber content in diets on heat production (HP) and NE:ME ratio and to determine the NE content and NE:ME ratio of full-fat rice bran (FFRB), defatted rice bran (DFRB), corn gluten feed (CGF), and corn germ meal (CGM) fed to growing barrows using indirect calorimetry (IC). Thirty growing barrows (28.5 ± 2.4 kg BW) were allotted in a completely randomized design to 5 dietary treatments that included a corn–soybean meal basal diet and 4 experimental diets with a constant ratio of corn and soybean meal (difference method) containing 30% FFRB, DFRB, CGF, and CGF. Pigs were housed in individual metabolism crates for 20 d including 14-d adaptation to the diet and 6 d to determine the HP and total collection of feces and urine in respiration chambers. Pigs were fed their respective diets at 550 kcal ME·kg BW(0.60−1)·d(−1) on the basis of BW measured on days 0, 7, and 14. The apparent total tract digestibility (ATTD) of DM, GE, and OM were greater (P < 0.01) in pigs fed the basal diet. The ATTD of DM, GE, and OM in pigs fed the DFRB diet were lesser (P < 0.01) when compared with those fed the basal and FFRB diets. The ATTD of ether extract (EE) in pigs fed the FFRB diet was greater (P < 0.01) compared with those fed basal, DFRB, CGF, and CGM diets. The HP adjusted for the same ME intake was greater (P < 0.01) in pigs fed the DFRB, CGF, and CGM diets compared with those fed basal and FFRB diets. The NE:ME ratio in pigs fed the FFRB diet was greater (P < 0.01) when compared with those fed the DFRB, CGF, and CGM diets. The NE content of FFRB, DFRB, CGF, and CGM determined using the IC method were 2,952, 1,100, 1,747, and 2,079 kcal/kg DM, respectively. The NE content of FFRB, CGF, and CGM determined using the IC method were 3.5%, 3.8%, and 1.8% greater, respectively, than the predicted values, whereas NE content of DFRB determined using the IC method was 2.1% lower than the predicted values. In conclusion, pigs fed the fiber-rich ingredients had greater HP and lower nutrient digestibility. However, pigs fed FFRB diets containing greater fat content had a lower heat increment and, therefore, higher utilization efficiency. The NE:ME ratio ranged from 71.6% to 82.4%. The NE of FFRB, DFRB, CGF, and CGM determined using the IC method were 2,952, 1,100, 1,747, and 2,079 kcal/kg DM, respectively.